2022
DOI: 10.3390/vaccines10010122
|View full text |Cite
|
Sign up to set email alerts
|

Cyberchondria, Fear of COVID-19, and Risk Perception Mediate the Association between Problematic Social Media Use and Intention to Get a COVID-19 Vaccine

Abstract: Vaccination is the most effective way to control the COVID-19 pandemic, but vaccination hesitancy threatens this effort worldwide. Consequently, there is a need to understand what influences individuals’ intention to get a COVID-19 vaccine. Restriction of information gathering on societal developments to social media may influence attitudes towards COVID-19 vaccination through exposure to disinformation and imbalanced arguments. The present study examined the association between problematic social media use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 59 publications
0
22
0
9
Order By: Relevance
“…Evidence indicated that the fear of COVID-19 could be an important factor contributing to vaccine hesitancy [ 65 , 66 ]. However, this factor was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicated that the fear of COVID-19 could be an important factor contributing to vaccine hesitancy [ 65 , 66 ]. However, this factor was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the existing literature highlights the influence of subjective perceptions and psychological factors on vaccine acceptance. People are more willing to get vaccinated if they have more infection- or health-related fears, or if they trust health officials’ dissemination of COVID-19-related information rather than relying on the information on social media [ 4 , 5 , 10 ]. Reich [ 18 ] found that parents with high levels of social privilege are more likely to refuse vaccines for their children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To enhance the progress of COVID-19 vaccination, the critical first step is to understand the underlying drivers behind unvaccinated individuals, particularly their hesitancy or skepticism about the service. Much of the fast-growing body of research on this topic emphasizes disparities in different sociodemographic groups’ attitudes or fears towards the available vaccines (e.g., [ 4 , 5 , 6 , 7 , 8 , 9 ]). It remains a challenge to effectively implement vaccine campaign strategies to target those population segments with under-vaccination rates.…”
Section: Introductionmentioning
confidence: 99%
“…54 Restrictions on social media collection of information about social development might affect attitudes toward COVID-19 vaccination through exposure to disinformation and imbalanced arguments. 55 Problematic social media use was significantly associated with psychological distress both directly and indirectly. 23 However, there was controversy over the role of the media in disseminating risk information.…”
Section: Media Risk Perception and The Intention To Engage In Protect...mentioning
confidence: 99%